Pengaruh Ownership Structure dan Board Governance Terhadap Dividend Payout Ratio - Eliza Andriani BR Surbakti; Adi Firman Ramadhan (Journal of Economics and Business, 2021)
This research aims to examine the effect of corporate governance on dividend policy. The ownership structure is divided into controlling ownership, government-controlled firm, foreign-controlled firm and board governance is divided to board independent and intensity as independent variables, while dividend payout ratio as dependent variable. Firm size, growth, return on assets, and leverage are also added as control variable. This research uses a sample consisting of 85 banking companies listed on Indonesia Stock Exchange in the period of 2013-2017. The purposive sampling method was used in selecting the research sample. Static panel data technique which was estimated using Tobit regressions are choosen for this research statistic analysis. The result of this research shows that controlling ownership and government-controlled firm have a positive significant effect on the dividend payout ratio, but foreign-controlled firm have a negative significant effect on the dividend payout ratio. Meanwhile, board independent and intensity have a positive but no significant effect on the dividend yield.